Pelaksanaan Alih Debitur Dalam Perjanjian Jual Beli Motor: (Studi Di FIF Group Cabang Selong Lombok Timur) - Apriyandi Akbar; Aris Munandar (Private Law, 2022)
The purpose of this study is to find out the implementation and legal consequences of the debtors transfer in motorbike sale agreement and legal protection of the parties in implementing debtors transfer in motorbike sale agreement. The method of this research is normative-empirical legal research using statute, conceptual and sociological approaches. The result of this research is that the implementation of debtors transfer conducted without permit of creditors is not valid. The legal consequence of debtors transfer in motorbike sale agreement is default and debtor conducted over credit without creditor permit is breach the Article 36 Law Number 42 of 1999 concerning Fiduciary. The second problem is about legal protection for the parties in implementing debtors transfer in motorbike sale agreement covers legal protection for creditors, PT FIF group, and debtors or consumers. The legal protection of creditors is regulated in Article 36 Law Number 42 of 1999 Concerning Fiduciary.